Utilizing Chair Massage to Address One Woman’s Health in Rural Ghana West Africa: a Case Report - Meryanos, LMT, AAS, Cathy J. (International Journal of Therapeutic Massage & Bodywork, 2016)
Background and Objectives: There is limited access to health care in rural Ghana and virtually no rehabilitative services available. This situation presents a unique opportunity to utilize chair massage in addressing women’s health in rural Ghana, particularly when it comes to muscle pain and fatigue from heavy labor. The objective of this case report is to determine the results of chair massage as a strategy to reduce neck, shoulder, and back pain, while increasing range of motion. Case Presentation: The patient is a 63-year old Ghanaian female, who was struck by a public transport van while carrying a 30–50 pound load on her head, two years prior. The accident resulted in a broken right humerus and soft tissue pain. A traditional medicine practitioner set the bone, however there was no post-accident rehabilitation available. At the time of referral, she presented complaints of shoulder, elbow, and wrist pain. In addition, she was unable to raise her right hand to her mouth for food intake. Results: The results of this case report include an increase in range of motion, as well as elimination of pain in the right shoulder, elbow, and hand. Visual assessments showed an approximate increase of ROM within the ranges of 45–65 degrees in the right arm, as well as 10–15 degrees in 4th and 5th fingers. There was also a decrease in muscle hypertonicity in the thoracic and cervical areas, and a profound increase in quality of life for the patient. Discussion: This case report illustrates how therapeutic chair massage was utilized to address a common health concern for one woman in rural Ghana. It also demonstrates that pre-existing musculoskeletal disorders and pain may be eliminated with massage intervention. Massage therapy may be important to ameliorating certain types of health problems in remote rural villages in low income countries.